2012
DOI: 10.1002/chem.201202748
|View full text |Cite
|
Sign up to set email alerts
|

New Liquid Crystalline Materials Based on Two Generations of Dendronised Cyclophosphazenes

Abstract: A divergent approach was used for the synthesis of dendritic structures based on a cyclotriphosphazene core with 12 or 24 hydroxyl groups, by starting from [N(3)P(3)(OC(6)H(4)OH-4)(6)] and using an acetal-protected 2,2-di(hydroxymethyl)propionic anhydride as the acylating agent. Hydroxyl groups in these first- and second-generation dendrimers, G1-(OH)(12) or G2-(OH)(24), were then condensed in turn with mono- or polycatenar pro-mesogenic acids to study their ability to promote self-assembly into liquid crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…For instance, there are several studies in the literature on the reactions of cyclotriphosphazenes with NO donor type difunctional reagents [4][5][6]. Some of the cyclotriphosphazene derivatives are used as liquid crystals [7,8], rechargeable lithium-ion batteries [9,10], OLEDs [11,12], and lubricants [13,14]. It is found that aminocyclophosphazene derivatives have antimicrobial activity against bacteria and fungi [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, there are several studies in the literature on the reactions of cyclotriphosphazenes with NO donor type difunctional reagents [4][5][6]. Some of the cyclotriphosphazene derivatives are used as liquid crystals [7,8], rechargeable lithium-ion batteries [9,10], OLEDs [11,12], and lubricants [13,14]. It is found that aminocyclophosphazene derivatives have antimicrobial activity against bacteria and fungi [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was found that spermine-bonded cyclotriphosphazenes disclosed cytotoxic activity against HT-29 (human colon adenocarcinoma), Hep2 (human epidermoid larynx carcinoma) and Vero (African green monkey kidney) cells and stimulated apoptosis [20]. Furthermore, some 1,4-dioxa-8-azaspiro [4,5] decane(DASD)-substituted ferrocenylphosphazenes were found to be effective against HeLa cancer cell lines [21]. In addition, aziridine-crown substituted cyclotriphosphazenes, known as the hazardous compounds, cleave the DNA and halt the growth of cancer cells [22].…”
Section: Introductionmentioning
confidence: 98%
“…Hexachloro cyclotriphosphazene (cyclic trimer, N 3 P 3 Cl 6 ) is a versatile starting compound for the syntheses of cyclotriphosphazene derivatives [1,2], polyorganophosphazenes [3,4] and dendrimers [5]. In the literature, a wide range of cyclotriphosphazene derivatives with different side groups and with diverse application potential were prepared using the replacement of highly reactive Cl-atoms in N 3 P 3 Cl 6 by a variety of -NH or -OH functionalized nucleophilic reagents, such as primary [6] and secondary amines [7], polyamines [8] and aryloxides [9].…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Following a similar approach, a family of dendrimers up to the second generation was prepared, containing cyclotriphosphazene as a central rigid core and dendrons derived from 2,2-bis(hydroxymethyl)propionic acid, functionalized on their surface with mono-and polycatenar pro-mesogenic units. [10] Caminade and Majoral have described a well-known family of phosphorus dendrimers, poly-(phosphorhydrazone) dendrimers (PPH), based on this type of rigid core. [13] Although very interesting applications of these dendrimers have been proposed in the fields of catalysis, medicinal chemistry, and materials science, [14] to the best of our knowledge there has been no report concerning the preparation of liquid-crystalline macromolecules based on this system.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Dendromesogens containing phosphorus atoms in their structures have been scarcely described in the literature. [9,10] Nevertheless, some of us have reported several series of unconventional mesogens derived from the cyclotriphosphazene ring, which can bear mesogenic units directly attached to the easily functionalized phosphorus atoms. [11,12] In those series, reaction of hydroquinone with hexachlorocyclotriphosphazene, followed by esterification of the peripheral hydroxyl groups with mono-or polycatenar benzoic acid derivatives, allowed the preparation of new liquid-crystalline compounds.…”
Section: Introductionmentioning
confidence: 99%